A theoretical model for investigating the thermo-mechanical performance of functionally graded rotating discs with varying grading index values - E. Saber; A. Abd_Elsalam (Forces in Mechanics, 2022)
The present study aims to develop a theoretical model to investigate the mechanical performance of functionally graded rotating discs with varying thickness profiles, made of copper alloy and tungsten with various values of grading index, when subjected to mechanical and thermal loads. The proposed new approach is to be used to evaluate the mechanical properties of the FGM used at different values of the reinforcement coefficient without the need to perform a large number of tests including temperature changes. The results showed that the use of wavy thickness profile improves the mechanical response of the annular disc subjected to mechanical/thermal load.